2018
DOI: 10.1590/s1519-99402018000100012
|View full text |Cite
|
Sign up to set email alerts
|

Performance and carcass characteristics of lambs ½ Dorper + ½ Santa Inês, slaughtered with different thicknesses of subcutaneous fat

Abstract: SUMMARY The aim of this study was to evaluate the effect of subcutaneous fat thickness (SFT) on slaughter in lambs ½ Dorper + ½ Santa Inês (DSI) on performance, carcass characteristics and commercial cuts. It was used twenty-four lambs, slaughtered with 2mm, 3mm and 4mm SFT. There was an effect of SFT on performance: for days of confinement (2mm = 51.38, 3mm = 66.50, 4mm = 91.63 days), age at slaughter (2mm = 139.38, 3mm = 159.88, 4mm = 171.00 days), final body weight (2mm = 33.50, 3mm = 42.81, 4mm = 46.19 kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
(4 reference statements)
1
7
0
1
Order By: Relevance
“…Animal performance data presented in this study showed positive results and is similar to results reported in the literature using Dorper breed and its cross-breeds [ 57 , 58 , 59 ]. The effect of high levels of yerba mate extract (4%) resulted in a reduction in dry matter intake and, consequently, a reduction in the general performance of the lambs; on the other hand, inclusions of up to 2% caused an increase in dry matter intake, total weight gain, and daily weight gain.…”
Section: Discussionsupporting
confidence: 89%
“…Animal performance data presented in this study showed positive results and is similar to results reported in the literature using Dorper breed and its cross-breeds [ 57 , 58 , 59 ]. The effect of high levels of yerba mate extract (4%) resulted in a reduction in dry matter intake and, consequently, a reduction in the general performance of the lambs; on the other hand, inclusions of up to 2% caused an increase in dry matter intake, total weight gain, and daily weight gain.…”
Section: Discussionsupporting
confidence: 89%
“…The precocity of most cuts in relation to the half carcass indicates that the Dorper breed contributed to the formation of a carcass with an accelerated growth and better cut yields (Cartaxo et al, 2017), providing desirable characteristics of compactness that are transmitted to its progeny (Nascimento et al, 2018). It should be noted that, despite their greater SFT and weights, these lambs did not reach physiological maturity in the present study, since their bone and muscle tissues continued to show accelerated growth.…”
Section: Resultsmentioning
confidence: 57%
“…The maintained growth rate of these tissues presupposes that the lambs had not yet reached their mature weight. Therefore, the SFT at slaughter did not affect the muscle yield of the carcass; however, a greater thickness of the subcutaneous fat may protect carcasses from losses during their freezing process (Nascimento et al, 2018).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations